Learning strategies used by Brazilian university students: a literature review (Research, Society and Development, 2021)
Academic success is the result of several variables that influence learning. One of these variables is the learning strategies used by the student, which can be defined as cognitive, behavioral and/or, emotional conscious procedures that seek to improve the knowledge retention and recovery process. The present article sought to examine how the learning strategies used by Brazilian university students have been investigated in the literature. The review was carried out using descriptors related to the phenomenon of interest (learning strategies, metacognition and, self-regulation) together with the expression “university students”. Only empirical articles were selected whose participants were Brazilian. The research corpus consisted of 25 studies published between 2005 and 2020. In most articles, it was possible to observe the students’ preference for metacognitive, reading, planning and, social strategies. Finally, the use of cognitive and metacognitive techniques obtained a positive correlation with the motivation intrinsic to learning and with greater expression of self-efficacy. The knowledge of the learning strategies and their use is relevant for the elaboration of intervention programs aimed at the development of strategies that promote academic success. The relevance of this review is to present an overview of how the topic has been investigated.